(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The “cloud” is considered as a collection of hardware, storage data, multiple applications, interfaces, services, and networks, that provide the way through which users and companies can access the infrastructures remotely via the Internet on-demand from anywhere, at any time, which are independent of locations. Also can be increasing capacity or dynamically incorporating without investment in new facilities, training or licensing new programs to new workers. It extends the IT capabilities currently. Cloud computing is a common option for users and businesses for several benefits including increased productivity, high execution speed, low computer costs, efficiency, improved performance, and data reliability. Because of these benefits, each business holder and organization wish to store their data in the cloud [1]. But as more data and files are being placed in the cloud by people and organizations, worries are beginning about how safe the environment is starting to rise. The ideal safety mechanism for user’s data in rest is to encrypt the data and store only the encrypted files into cloud storage, where providers of cloud or any unauthorized party unable to access the encryption key. So we need to use one or more cryptographic algorithms and protocols to encrypt the user’s data before transfer to the clouds [2]. The main aim of this particular research is to protect the transmitted data with the help of encryption and decryption techniques. This research paper presents a new model for encrypting the data transmitted through cloud. The algorithms used in this model are: new lightweight hybrid encryption algorithm. We proposed to apply a hybrid of one part from PRESENT algorithm (PA) and another from TWINE algorithm (TA) by using different chaos keys in both encryption and decryption. For making the cloud more secure and to Confidence the data. The algorithm Chaos Keys Generation was used to produce random numbers by using a new chaos system with different initials and parameter values in order to generate 5-D chaos keys.